- Cho đa thức f(x) = [tex]a_{4}x^{4} + a_{3}x^{3} + a_{2}x^{2} + a_{1}x + a_{0}[/tex] . Biết rằng f(1) = f(-1) và f(2) = f(-2). CM : f(x) = f(-x) với mọi x
-Ta có:
$f(1)=a4+a3+a2+a1+a0$
$f(-1)=a4-a3+a2-a1+a0$
$ f(1)=f(-1)\Rightarrow a4+a3+a2+a1+a0=a4-a3+a2-a1+0$
$\Leftrightarrow a4+a3+a2+a1+a0-a4+a3-a2+a1=0$
$\Leftrightarrow 2a3+2a1=0$
$\Leftrightarrow 2(a3+a1)=0$
$\Leftrightarrow a3+a1=0(1)$
-Lại có:
$f(2)=a4.2^4+a3.2^3+a2.2^2+a1.2+a0$
$f(-2)=a4.(-2)^4+a3.(-2)^3+a2.(-2)^2+a1.(-2)+a0$
$=a4.2^4+a3.(-2)^3+a2.2^2+a1.(-2)+a0$
$f(2)=f(-2)\Rightarrow a4.2^4+a3.2^3+a2.2^2+a1.2+a0=a4.2^4+a3.(-2)^3+a2.2^2+a1.(-2)+a0$
$\Leftrightarrow a4.2^4+a3.2^3+a2.2^2+a1.2+a0-a4.2^4-a3.(-2)^3-a2.2^2-a1.(-2)-a0=0$
$\Leftrightarrow a3.2^3-a3.(-2)^3+a1.2-a1(-2)=0$
$\Leftrightarrow a3[2^3-(-2)^3]+a1(2+2)=0$
$\Leftrightarrow 16.a3+4a1=0$
$\Leftrightarrow 4(4a3+a1)=0(2)$
-Suy ra:$(1)=(2)\Leftrightarrow a3+a1=4a3+a1$
$\Leftrightarrow a3+a1-4a3-a1=0$
$\Leftrightarrow (-3)a3=0$
$\Leftrightarrow a3=0$
-Mà: $a3+a1=0\Rightarrow a1=0$.
-Lại có:
$f(x)=a4.x^4+0+a2.x^2+0+a0(3)$
$f(-x)=a4.(-x)^4+0+a2.(-x)^2+0+a0$
$=a4.x^4+0+a2+x^2+0+a0(4)$
$\Rightarrow (3)=(4)=>đpcm$
Bài này 'thú dzị' thật @,@